Association of thyroid dysfunction and COVID-19: A systematic review and meta-analysis - Darvishi, Mohammad; Nazer, Mohammad Reza; Shahali, Hamze; Nouri, Majid (Frontiers in Endocrinology, 2022)
This systematic review and meta-analysis was conducted aiming to evaluate the effect of COVID-19 on thyroid function and the role of thyroid hormones alterations in predicting the severity of COVID-19. Online databases including Scopus, Medline/PubMed, EMBASE, Google Scholar, and Cochrane were searched up to December 28th, 2020. After screening titles, abstracts, and full manuscripts, respectively, 16 reports were enrolled. The risk of bias (ROB) was evaluated using the QUADAS-2 tool. In addition, odds ratio (OR) and hazard ratio (HR) analysis for evaluating the OR of abnormal thyroid function tests (TFT) in predicting the COVID-19 severity and mortality, respectively. Sensitivity, specificity, and cut-off value analysis were also conducted for thyroid-stimulating hormone (TSH) levels. Among 16 enrolled studies, ROB of the current study is estimated low to moderate. The average number of patients in each study was 481 (range: 50,703), with an overall mean age of 55.8 ± 18.5, and the female proportion of 40.7%. Overall, the pooled analysis showed that the prevalence of thyroid dysfunction among 8,807 COVID-19 cases was 7.02%. Among mild to moderate COVID-19 patients, 64 patients had abnormal TFT (3.1%), and among patients who experienced severe to critical COVID-19, 44 patients had abnormal TFT (8.3%). Our results showed that the overall OR for abnormal TFT and the severity of COVID-19 obtained from 2,562 COVID-19 patients was 4.21 (1.2, 15.2). The mean HR of TSH level of COVID-19 mortality was 1.40 (0.85, 2.32). TSH lower than 1.09 had a likelihood ratio of 13.12 with a sensitivity of 57.9% (42.19%, 72.15%) and specificity of 95.59% (90.71% to 97.96%) for predicting the COVID-19 severity. Our results indicate a 4.2 fold association between abnormal TFT and the severity of COVID-19 in comparison to patients with normal TFT, and patients with TSH lower than 1 had a 1.40-fold higher risk of death in comparison with patients with normal TSH.